Shakespearean Libretti in Music History: an Overview with Special Reference to Italian Librettist Arrigo Boito - Radoš-Perković, Katja (2008)
The paper proides an overview of major musical pieces based on Shakespeare's works, focusing on those most frequently used. Since the best Shakespearean libretti are to be found in Italian literary and music history, it also deals with the work of Arrigo Boito, librettist for Verdi's masterpiece operas "Otello" and "Falstaff".
Projekt MZOS
ENG